American grand strategy under Obama : competing discourses - Löfflmann, Georg (Edinburgh University Press, 2017)
This book explores how rivalling discourses of American grand strategy reveal a fractured consensus of geopolitical identity and national security under President Obama. This conflict manifested in divergent elite visions of liberal hegemony, cooperative engagement and unilateral restraint. Georg Lofflmann examines the identity conflict within the Washington foreign policy establishment, between elite insiders and outsiders, and how the 'Obama Doctrine' both confirmed a geopolitical vision of American exceptionalism and challenged established notions of US hegemony and world leadership.